PENINGKATAN KOMPETENSI PENGELOLAAN SIMPAN PINJAM DALAM MENGOPTILAMKAN KUALITAS LAPORAN KEUANGAN KOPERASI MERAH PUTIH SAWANGAN - Walidain, Birrul; Wardani, Ni Made Sri; Maelani, Puspita; Saputro, Maulana Agung; Sari, Cynthia Dikna (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The background to this activity is the existence of problems in the management of savings and loans at the Merah Putih Sawangan Cooperative, which is still carried out manually, a lack of understanding among administrators in recording inventory, and difficulties in preparing cooperative financial reports. The objective of this training is to provide knowledge and skills to cooperative administrators regarding savings and loan management, inventory recording, and the preparation of cooperative financial reports in order to improve the quality of management and reporting. The activity method uses a training approach with stages of observation, training implementation surveys, and evaluation of activity results, with the training participants being the administrators of the Merah Putih Sawangan Cooperative. The training results based on pretest and posttest scores show an increase in the administrators' understanding of savings and loan management, systematic inventory recording, and the preparation of quality financial reports. This training activity is evaluated on an ongoing basis.